The role of vitamin B6 as an antioxidant in the presence of vitamin B2-photogenerated reactive oxygen species. A kinetic and mechanistic study - Natera, Jose Eduardo (2012)
We report on the photostability of a mixture of vitamins B6 and B2 (riboflavin, Rf) upon visible light irradiation and on the possible role of the vitamin B6 family (B6D) as deactivators of reactive oxygen species (ROS). The work is a systematic kinetic and mechanistic study under conditions in which only Rf absorbs photoirradiation. Pyridoxine, pyridoxal hydrochloride, pyridoxal phosphate and pyridoxamine dihydrochloride were studied as representative members of the vitamin B6 family. The visible light irradiation of dissolved Rf and B6D in pH 7.4 aqueous medium under aerobic conditions induces photoprocesses that mainly produce B6D degradation. The overall oxidative mechanism involves the participation of ROS. Photogenerated 3Rf∗ is quenched either by oxygen, giving rise to O2(1Δg) by electronic energy transfer to dissolved ground state oxygen, or by B6D yielding, through an electron transfer process, the neutral radical RfH•, and O2•- in an subsequent step. B6D act as quenchers of O2(1Δg) and O2•-, the former in a totally reactive event that also inhibits Rf photoconsumption. The common chromophoric moiety of B6D represented by 3-hydroxypyridine, constitutes an excellent model that mimics the kinetic behavior of the vitamin as an antioxidant towards Rf-generated ROS. The protein lysozyme, taken as an O2(1Δg)-mediated oxidizable biological target, is photoprotected by B6D from Rf-sensitized photodegradation through the quenching of electronically excited triplet state of the pigment, in a process that competes with O2(1Δg) generation.